Modulation of aroma and chemical composition of Albarino semi-synthetic wines by non-wine Saccharomyces yeasts and bottle aging - Perez, Maria Dolores; Denat, Marie; Minebois, Romain; Heras, Jose Maria; Guillamon, Jose Manuel; Ferreria, Vicente; Querol, Amparo (Elsevier, 2022)
Saccharomyces yeasts from different origins and species fermented in a semi-synthetic must containing aroma precursor of cv. Albari˜no and polyfunctional mercaptans precursors. The resulting wines were subjected to accelerate anoxic aging. Afterward, aroma profiles were analyzed by distinct gas chromatography methodologies. Cryotolerant strains showed better fermentation performances with significant differences in volatile and nonvolatile fermentation products than Saccharomyces cerevisiae (S. cerevisiae). We suggested that the highest levels γ-butyrolactone and diethyl succinate in Saccharomyces uvarum (S. uvarum) strains, together with their substantial succinic acid yields, could be related to greater flux through the GABA shunt. These strains also had the highest production of β-phenylethyl acetate, geraniol, and branched-chain ethyl esters. The latter compounds were highly increased by aging, while acetates and some terpenes decreased. S. kudriavzevii strains showed a remarkable ability to release polyfunctional mercaptans, with SK1 strain yielding up to 47-fold and 8-fold more 4-methyl-4-mercaptopentan-2-one (4MMP) than S. cerevisiae and S. uvarum strains, respectively. The wild S. cerevisiae beer isolate showed a particular aroma profile due to the highest production of ethyl 4-methylvalerate (lactic and fruity notes), γ-octalactone (coconut), and furfurylthiol (roasted coffee). The latter compound is possibly produced from the pentose phosphate pathway (PPP). Since erythritol, another PPP intermediate was largely produced by this strain.